The fracture resistance of a CAD/CAM Resin Nano Ceramic (RNC) and a CAD ceramic at different thicknesses - Chen, Chenfeng; Trindade, Flavia Zardo [UNESP]; Jager, Niek de; Kleverlaan, Cornelis J.; Feilzer, Albert J. (Elsevier B.V., 2014)
Objective. This study aimed to investigate the influence of restoration thickness to the fracture resistance of adhesively bonded Lava (TM) Ultimate CAD/CAM, a Resin Nano Ceramic(RNC), and IPS e. max CAD ceramic.Methods. Polished Lava (TM) Ultimate CAD/CAM (Group L), sandblasted Lava (TM) Ultimate CAD/CAM (Group LS), and sandblasted IPS e.max CAD (Group ES) discs (n=8, phi=10 mm) with a thickness of respectively 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, and 3.0 mm were cemented to corresponding epoxy supporting discs, achieving a final thickness of 3.5 mm. All the 120 specimens were loaded with a universal testing machine at a crosshead speed of 1 mm/min. The load (N) at failure was recorded as fracture resistance. The stress distribution for 0.5 mm restorative discs of each group was analyzed by Finite Element Analysis (FEA). The results of facture resistances were analyzed by one-way ANOVA and regression.Results. For the same thickness of testing discs, the fracture resistance of Group L was always significantly lower than the other two groups. The 0.5 mm discs in Group L resulted in the lowest value of 1028 (112) N. There was no significant difference between Group LS and Group ES when the restoration thickness ranged between 1.0 mm and 2.0 mm. There was a linear relation between fracture resistance and restoration thickness in Group L (R = 0.621, P < 0.001) and in Group ES (R = 0.854, P < 0.001). FEA showed a compressive permanent damage in all groups.Significance. The materials tested in this in vitro study with the thickness above 0.5 mm could afford the normal bite force. When Lava Ultimate CAD/CAM is used, sandblasting is suggested to get a better bonding. (C) 2014 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Fracture resistance; CAD/CAM; Restoration thickness; Resin Nano Ceramic; Dental ceramic